Local Confluence Analysis of Consistent EMF Transformations - Biermann, Enrico (Electronic Communications of the EASST, 2011)
Model transformation is one of the key activities in model-driven software development. An increasingly popular technology to define modeling languages is provided by the Eclipse Modeling Framework (EMF). Several EMF model transformation approaches have been developed, focusing on different transformation aspects. For the analysis of model transformations, graph transformation techniques provide a formal basis and tool support. In this paper we aim to make use of those techniques by providing a formal foundation of consistent EMF transformations to analyze critical pairs between EMF transformation rules as well as extending the notion of local confluence to EMF transformation systems. The analysis is also demonstrated on a small example simulating the firing behavior of elementary Petri nets.